(untitled) (Nepal Journal of Environmental Science, 2024)
Incense burning is a common practice in many Asian countries, often used at homes to mask bad odors and repel insects. Pollutants released from incense burning can quickly accumulate to hazardous levels in indoor environments, particularly in poorly ventilated areas. Particulate matter (PM) emitted from incense is of great importance due to its adverse effects on human health. The study focuses on the measurement of PM2.5, and CO2 concentrations in Bangalamukhi temple located in Lalitpur, Nepal. The data were collected using an Air Visual Pro (IQAir, Switzerland). The air quality parameters were measured for two days during the Navaratri (Dashain) festival designated as Peak Period I and II, and on Thursday as Peak Period III, considering the higher flow of people during these days. Non-peak Periods I and II were defined as any other days except Thursday and/or Saturday, assuming a lower flow of people. The RH levels during the sampling periods ranged from 47-72% and ambient temperature ranged from 13.7-29.0. The study showed the maximum hourly average PM2.5 concentrations during peak and non-peak period days at Bangalamukhi temple exceeded the National Ambient Air Quality Standards 2012. Furthermore, the peak value of PM2.5 concentration during both the peak period days (peak period I and II) was significantly higher than in the samples conducted during all the non-peak period days at the sampling site (peak value PM2.5 concentration: 439.40-118.8 vs 215.1-55.4), indicating that the burning of incense was responsible for the elevated PM2.5 concentration in the temple premises.